New tractors for old - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
In many developing countries up to 30% of tractors are standing idle because of a lack of replacement parts. Surveys indicate that in Africa alone there are some 100,000 tractors in a state of disrepair. Machinery graveyards have become all too...